Research on education in Africa, the Caribbean, and the Middle East, an historic overview - Mutua, Kagendo, 1966-; Sunal, Cynthia S. (Research on education in Africa, the Caribbean, and the Middle East., 2004)
A historical overview of research on education in Africa, the Caribbean and the Middle East. Topics covered include: the challenges and assistance of beginning teaching in Jamaica; learning cognitive skills in Israel; and a feminist analysis of sexual harassment among high school girls in Kenya.